Fatigue Effect On Cross-Talk In Mechanomyography Signals Of Extensor And Flexor Forearm Muscles During Maximal Voluntary Isometric Contractions - Mohamad Ismail, Mohamad Razif; Chee, Kiang Lam; Rahiman, Mohd Hafiz Fazalul; Sundaraj, Kenneth (International Society of Musculoskeletal and Neuronal Interactions, 2021)
Objective: This paper presents the analyses of the fatigue effect on the cross-talk in mechanomyography (MMG) signals of extensor and flexor forearm muscles during pre-and post-fatigue maximum voluntary isometric contraction (MVIC). Methods: Twenty male participants performed repetitive submaximal (60% MVIC) grip muscle contractions to induce muscle fatigue and the results were analyzed during the pre-and post-fatigue MVIC. MMG signals were recorded on the extensor digitorum (ED), extensor carpi radialis longus (ECRL), flexor digitorum superficialis (FDS) and flexor carpi radialis (FCR) muscles. The cross-correlation coefficient was used to quantify the cross-talk values in forearm muscle pairs (MP1, MP2, MP3, MP4, MP5 and MP6). In addition, the MMG RMS and MMG MPF were calculated to determine force production and muscle fatigue level, respectively. Results: The fatigue effect significantly increased the cross-talk values in forearm muscle pairs except for MP2 and MP6. While the MMG RMS and MMG MPF significantly decreased (p<0.05) based on the examination of the mean differences from pre-and post-fatigue MVIC. Conclusion: The presented results can be used as a reference for further investigation of cross-talk on the fatigue assessment of extensor and flexor muscles’ mechanic.